Effects of meteorological conditions in efficiency of solar photovoltaic panels - Abbagu, Eduard A.
This paper aimed to determine the effects of ambient temperature, atmospheric pressure, relative humidity, wind speed, and irradiance on solar photovoltaic (PV) panels' performance located at tropical coastal areas, particularly in Batangas City, a southwest region of the Philippines. The effects of coastal areas' meteorological conditions on the efficiency of two types of solar PV panels namely monocrystalline and polycrystalline panels were investigated and analyzed. Due to the tropical location and archipelagic structure of the Philippines, the effects of meteorological conditions on the solar PV panels are rather complicated, leading to noticeable variation of energy outputs within a year. Temperature has the most impact on the efficiencies of both monocrystalline and polycrystalline panels. Monocrystalline panel can operate at higher temperature compared to polycrystalline panel. Based on its efficiency and reaction to temperature, monocrystalline panel is more superior to polycrystalline panel.